Aplicação de xilanases fúngicas no processo de branqueamento da polpa kraft pelas indústrias de papel - Kmetzki, Ana Carolina Feil (2018)
The pulp and paper industry is a globally expanding segment. Focusing on economic profitability and environmental preservation, the paper industry has been looking for viable alternatives to enhance the Kraft process. The chlorine bleaching conventional method, although highly efficient, causes environmental pollution due to the discharge of organochlorine compounds into effluents. The use of enzymes microorganisms, especially xylanases, has emerged as a promising alternative for the bleaching processes. These enzymes could considerably help reduce environmental pollution, reducing the use of organochlorine compounds, which acts as a bleaching chemical for pulps and causes the formation of organochlorine residual compounds, which are extremely harmful to the environment and give the pulp industry one of the most polluting. Therefore, studies that provide the use of enzymatic processes in the Kraft pulp bleaching stage by the industry will always be relevant, mainly in order to reduce the discharge of contaminating material into effluents. In this context, this review will discuss the characteristics of the constitution of the raw material for the pulp kraft paper industry, as well as the enzymatic properties of fungal xylanases cellulase-free tested on cellulose pulps, kraft and waste straw, which have potential for future use by paper industry.